Fashion Aesthetics in Contemporary Arab Sculpture - Alaa Issa Karim; Ali Abdullah Abood (Basrah Arts Journal, 2023)
The art of sculpture in the Arab world formed a solid foundation in the field of art through the various sculptural products presented by Arab sculptors in employing art through which they contributed to the reflection of the cultural heritage due to the forms, symbols, images, forms of clothing and their external formal influences that were included in their works, which reflected the aesthetics of fashion in Arab sculpture. Contemporary, which necessitated highlighting the knowledge of its aspects from the cognitive, social, artistic and cultural aspects, and the connotations expressed by the Arab sculptor in dress, and to know the cultural value and employ it in the sculptural work, through which it is possible to differentiate between one country and another in terms of culture, traditions, and knowledge of the segments of society that were the basis for the variation in people's daily lives. The current research includes four chapters, the first chapter of which includes the research problem, which becomes clear through the following question: What are the aesthetic values ​​achieved by fashion in contemporary Arab sculptural work, as well as the importance of research and the need for it, which lies in the fact that it represents a reflection of the aspects of traditional Arab life. The current research aims to identify the aesthetics of fashion in contemporary Arab sculpture. The research is limited spatially to sculptural works in the Arab world, temporally from 1950 to 2020, and objectively by studying sculptural works that reflect the aesthetics of contemporary Arab fashion.